Implementasi Pengembangan Kreativitas Pendidik di Madrasah Tsanawiyah Negeri 2 Medan - Syamsu Nahar; Mohammad Al-Farabi; Zulham Siregar; M Fajri Syahroni Siregar (TADRIS: Jurnal Pendidikan Islam, 2021)
This study describe and analyze 3 research focuses. First, to describe the teacher creativity development program at Madrasah Tsanawiyah Negeri 2 Medan. Second, to describe the implementation of the development of teacher creativity at Madrasah Tsanawiyah Negeri 2 Medan. Third, to describe the results achieved in the development of teacher creativity at Madrasah Tsanawiyah Negeri 2 Medan. This study uses descriptive qualitative methods, namely to describe, describe and reveal the results of research regarding the development of teacher creativity. Data collection techniques using interviews, observation, and documentation. The interactive model data analysis technique from Miles and Hubermen uses three stages, namely: data reduction, data presentation, and drawing conclusions.